2006
DOI: 10.1037/0021-843x.115.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Stress exposure and stress generation in child and adolescent depression: A latent trait-state-error approach to longitudinal analyses.

Abstract: In 2 longitudinal studies of negative life events and depressive symptoms in adolescents (N = 708) and in children (N = 508), latent trait-state-error structural equation models tested both the stress generation hypothesis and the stress exposure hypothesis. Results strongly suggested that self-reports of depressive symptoms reflect the influence of a perfectly stable trait factor as well as a less stable state factor. Support emerged for both the stress generation model and the stress exposure model. When the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
120
6
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(143 citation statements)
references
References 49 publications
(65 reference statements)
15
120
6
2
Order By: Relevance
“…However, girls exhibited higher levels of relative stability in the depression models when compared to boys, whereas middle to late adolescent exhibited higher levels of relative stability in the aggression models when compared to early to middle adolescents. Even though differences in relative stability are generally thought to affect the magnitude of cross-lagged associations (e.g., Cole et al, 2006), the gender and age cohort differences in stability paths we found do not seem to have a significant effect on cross-lagged associations.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…However, girls exhibited higher levels of relative stability in the depression models when compared to boys, whereas middle to late adolescent exhibited higher levels of relative stability in the aggression models when compared to early to middle adolescents. Even though differences in relative stability are generally thought to affect the magnitude of cross-lagged associations (e.g., Cole et al, 2006), the gender and age cohort differences in stability paths we found do not seem to have a significant effect on cross-lagged associations.…”
Section: Discussioncontrasting
confidence: 73%
“…However, personality traits or problem behavior symptoms may turn out to be so stable that little variance remains left to be explained by other variables. To overcome this problem, Cole et al (2006) applied Trait-State models to depression data in which a perfectly stable component (i.e., trait) and the part of the construct that does change (i.e., state) are distinguished. With this approach, Cole et al (2006) showed that the effects of negative events on depression became much stronger once the trait component was statistically controlled for.…”
Section: Strengths and Limitations Of The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Previously Cole et al (2006) demonstrated that biannual reports of discrete life event occurrence and impact were correlated over a few years' time in both elementary and middle school samples. Harkness et al (2006) have also reported that retrospectively reported childhood abuse and neglect were associated with greater levels of chronic difficulties in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Early adversity may be a marker of continuing exposure to negative stressors, such that those with exposure to childhood negative events and circumstances are more likely to continue to be exposed to stressful events and circumstances (Pearlin, 1989), especially adolescents who are still living at home. Several investigators have demonstrated that the number of adversities and life events experienced in childhood and adolescence is associated with the number of life events and chronic stressors experienced even into adulthood Turner & Butler, 2003;Turner & Turner, 2005), and Cole et al (2006) demonstrated considerable continuity in burden and number of life events in middle and elementary school samples. Some of the effects of early adversity on adolescent depression may be due less to their special status as 'early' as to their continuity with later stressors.…”
Section: Introductionmentioning
confidence: 99%